The Influence of Social Media and Lifestyle on Purchasing Decisions of Toko Kami Coffee Mediated by Brand Awareness - Satria, Dimas; Listiana, Erna; Ahmadi, Ahmadi; Barkah, Barkah; Fitriana, Ana (Primary Journal of Multidisciplinary Research, 2025)
This study aims to identify the impact of marketing through social media and lifestyle on purchasing decisions, with brand awareness as a connecting variable. The research design applied is causal research. A total of 220 Toko Kami consumers in Pontianak City were asked to fill out a questionnaire to collect data. The measurement model and structure of the research construct that is being developed are then analyzed using the Structural Equation Modeling (SEM) approach with the help of Smart PLS 4.0 statistical software. The findings of the study prove that Social Media Lifestyle Marketing and Lifestyle have a positive and significant effect on Purchase decisions and Brand Awa5reness. In addition, these two variables also affect Purchase Social media marketing decisions directly and indirectly, with Brand Awareness acting as a mediator. Brand Awareness also plays an important role, both as a direct factor and as a mediator in the relationship between Social Media and purchase decisions. This indicates that building strong brand awareness through consumer experiences will have a positive impact on loyalty and repurchase interest. This research is expected to provide valuable insights for business actors in developing effective marketing strategies in the digital era.